Optimal redistribution and education signaling - Spencer Bastani; Tomer Blumḳin; Luca Micheletto (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
This paper studies optimal taxation of income and education when employers cannot observe workers' productivity and workers signal their productivity to firms by choosing both quantity and quality of education. We characterize constrained efficient allocations and derive conditions under which there is predistribution, i.e., redistribution through wage compression. Implementation through income and education dependent taxes is discussed, as well as education mandates. A key insight is that achieving predistribution requires complementing the income tax with additional policy instruments that regulate the flow of information in the labor market and prevent high-skilled individuals from separating themselves from their low-skilled counterparts.
Keywords: D82; H21; H52; J31; 330; nonlinear taxation; education; asymmetric information; human capital; predistribution